The effects of Return on Equity Ratio, Debt to Equity Ratio, Current Ratio to Earning Per Share in manufacturing industries listed on Indonesian Stock Exchange during the period of 2015-2017 - Cindy Cindy; Karlina Chandra; Nuraini Nuraini; Winda Winda; Ronald Hasudungan Rajagukguk; Antonius KAP Simbolon (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
The objective of this research is to observe the effects of Return on Equity Ratio, Debt to Equity Ratio, Current Ratio to Earning Per Share in manufacturing industries listed on Indonesian Stock Exchange during the period of 2015-2017. The method used in this research is quantitative research approach, while inferential statistical research is used for the type of research. The object of this research is the manufacturing industry listed on Indonesian Stock Exchange during the period of 2015-2017. By using purposive sampling technique, 82 manufacture industries from Indonesian Stock Exchange during the period of 2015-2017 are obtained. The results show that partially Return on Equity Ratio has a positive and significant effect on Earning Per Share while partially Debt to Equity Ratio and Current Ratio have a negative and significant effect on the Earning Per Share. Simultaneously Return on Equity Ratio, Debt to Equity Ratio, and Current Ratio affect the Earning Per Share in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017.